Strengthen Thai Airline Industry Competitiveness in AEC-China Market: A Better Position Post Pandemic - Inprasertkul, Thanapol; Thanomkiat, Angkana (วารสารเพื่อการพัฒนาการท่องเที่ยวสู่ความยั่งยืน, 2024)
The effects of the COVID-19 pandemic were felt throughout many industries in Thailand, but certainly one of the most heavily affected was the airline industry. Since this was not an issue seen only in Thailand but throughout all of Southeast Asia and the rest of the world, it creates a major opportunity for Thailand to push forward and possibly take a larger stake in the airline industry within the AEC-China market while recovery is happening. Therefore, this article aims to explore the effective strategies, policies, and practices used by airlines as a vital tool for their business survival and competitiveness and to propose some implications that could help strengthen the Thai airline industry’s competitiveness in the AEC-China market after the pandemic. This article found that Thai airlines should expand their hub and spoke system in cooperation with the airport authorities, implement the ASEAN Single Aviation Market (ASAM) system and airline alliances, allow larger airline and legacy airlines within Thailand to focus more directly on long-haul international passenger and cargo transportation, open up smaller carriers within the country to increase their domestic and short-haul route numbers, and lastly, place an emphasis on passengers who travel to Thailand for medical tourism by finding ways to enter partnerships with some of the hospitals, which has the potential for incredible outcomes. Thus, it is hoped that the implications suggested in this article will help increase Thai airlines’ competitiveness in the AEC-China market and recover from post-pandemic issues.